2015
DOI: 10.1016/j.ebcr.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of focal symptomatic refractory status epilepticus with and without invasive EEG

Abstract: PurposeNeurosurgery appears to be a reasonable alternative in carefully selected patients with refractory status epilepticus (RSE) and super-refractory status epilepticus (SRSE). We discuss the optimal timing of the surgery and the use of previous stereoelectroencephalography (SEEG) invasive evaluation.MethodsWe identified 3 patients (two pediatric and one adult) who underwent epilepsy surgery because of RSE or SRSE from our epilepsy surgery database, one of them with previous SEEG.ResultsStatus epilepticus re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…A right anterior temporal lobectomy was planned, however the amygdala and hippocampus were not resected because of bleeding and congestive edema in the lesion area. Refractory status resolved after surgery and she attained long term seizure freedom over 4 years [32] .…”
Section: Discussionmentioning
confidence: 96%
“…A right anterior temporal lobectomy was planned, however the amygdala and hippocampus were not resected because of bleeding and congestive edema in the lesion area. Refractory status resolved after surgery and she attained long term seizure freedom over 4 years [32] .…”
Section: Discussionmentioning
confidence: 96%
“…Hemispherectomy for the refractory status epileptics was first reported in 2004 where anatomic hemispherectomy was done on a 7-year boy with cortical dysplasia in RSE [16] . The first 2 adult cases of hemispherotomy for RSE was reported by Oderiz et al in 2015 [17] followed by two more adult cases reported by McGinity M et al in 2016 [11] . Until now, only four cases of hemispherotomy for RSE in adults have been reported [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to extensive spatial sampling with modern systems now including more than 300 specialized sensors distributed over the surface of the head, source localization accuracy with MEG can be high, reaching 2 to 3 mm , but this relationship is variably dependent on the size and pathology of the underlying epileptic lesion (Bast et al, 2004;Widjaja et al, 2008;Mu et al, 2014). A high level of data concordance between MEG and these studies, as well as with invasive investigatory techniques such as stereoelectroencephalography (SEEG) or electrocorticography (ECoG), is associated with more favorable surgical outcomes (Cuello-Oderiz et al, 2015;Murakami et al, 2016). MEG can be very helpful in localization of non-lesional, multi-lesional, and extratemporal epilepsies, which tend to be especially prevalent in children, as approximately 50% of surgical cases in children have an underlying etiology of dysplasia or brain malformation (Jung et al, 2013;Albert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%